2011
DOI: 10.1007/s10815-011-9670-1
|View full text |Cite
|
Sign up to set email alerts
|

Male infertility in Northeast China: a cytogenetic study of 135 patients with non-obstructive azoospermia and severe oligozoospermia

Abstract: For infertile men in Northeast China, chromosome analysis is a necessary part of routine genetic testing, and the contributing effects of high smoking and alcohol consumption rates of this population should be discussed during genetic counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
2
12
3
Order By: Relevance
“…Oates et al [27] have reported that the mean FSH in the severely oligospermic men was significantly less than the mean of the azoospermic men, and the mean LH and T values did not differ significantly between the groups. Zhang et al [28] observed significant differences in the level of FSH between the two groups studied (nonobstructive azoospermic and severe oligozoospermic). Studies by Wang et al [26] and by Balkan et al [1] also show higher FSH and LH levels in men with severe spermatogenic failure, and this suggests that some of these men may have mild forms of the testicular dysgenesis syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Oates et al [27] have reported that the mean FSH in the severely oligospermic men was significantly less than the mean of the azoospermic men, and the mean LH and T values did not differ significantly between the groups. Zhang et al [28] observed significant differences in the level of FSH between the two groups studied (nonobstructive azoospermic and severe oligozoospermic). Studies by Wang et al [26] and by Balkan et al [1] also show higher FSH and LH levels in men with severe spermatogenic failure, and this suggests that some of these men may have mild forms of the testicular dysgenesis syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…At least 20 metaphases were analyzed per patient. Chromosomal abnormalities were described according to the International System for Human Cytogenetic Nomenclature (Mitelman et al, 1995;Zhang et al, 2012).…”
Section: Chromosome Analysismentioning
confidence: 99%
“…Klinefelter's syndrome (KFS) is the most frequent chromosomal anomaly observed among infertile men (Mitra et al, 2006;Choe et al, 2007;Wang et al, 2010;Behulova et al, 2011;Zhang et al, 2012). Although most men with KFS have the 47,XXY karyotype, some show the mosaic karyotype (KFM) in their somatic and germ cells (Mitra et al, 2006;Choe et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Among these infertile couples, approximately 50% could be attributed to male factors (Elfateh et al., ). Male infertility could be caused by a variety of factors, such as endocrine disorders, spermatic duct obstruction, antisperm antibodies, cryptorchidism, testicular trauma and so on (Zhang et al., ). Nonobstructive azoospermia (NOA), an infrequent cause of male infertility, remains unexplained and is often considered to be idiopathic male infertility (Suganya et al., ).…”
Section: Introductionmentioning
confidence: 99%